PENGGUNAAN MATEMATIKA REALISTIK INDONESIA DALAM MENGEMBANGKAN KEMAMPUAN DISPOSISI MATEMATIS SISWA PADA MATERI ALJABAR DI SALAH SATU SMP DI PALEMBANG [APPLYING THE INDONESIAN REALISTIC MATHEMATICS IN DEVELOPING STUDENTS’ MATHEMATICAL DISPOSITION ABILITY ON ALGEBRIC MATERIAL IN ONE OF THE JUNIOR HIGH SCHOOLS IN PALEMBANG] - Girsang, Revendi April Saputra; listiani, Tanti (Universitas Pelita Harapan, 2023)
The low level of mathematical disposition ability of the students in one of the Junior High Schools in Palembang became a special matter during the field experience. It was found that the average percentage of students' mathematical disposition ability was 53.01% in the moderate category. In addition, there were students who had a view of mathematics as a difficult and unpleasant science. In fact, mathematical disposition has a great influence on students' mathematics learning and achievement. Moreover, it will help students to see the beauty of God's creation through mathematics if they have a good mathematical disposition. This makes the Indonesian Realistic Mathematics Approach (PMRI) an alternative solution to the problem of mathematical disposition. The purpose of writing this thesis was to find out whether the application of PMRI could develop the disposition ability of algebra material and to describe the application of PMRI in developing the mathematical disposition ability of students in algebra material using a descriptive qualitative method. The results and conclusions of this paper show that the students' mathematical disposition ability after the application of PMRI increased with an average percentage result to 61.48% in the good category. The increase was caused by the mathematical disposition indicators that were refined in all PMRI syntax. Thus, these indicators can be refined in any syntax. Reflecting on the application of PMRI, it is suggested that the application can be done more than twice and use physical learning media.BAHASA INDONESIA ABSTRACT: Rendahnya kemampuan disposisi matematis siswa di salah satu SMP di Palembang menjadi perhatian khusus saat dilakukannya praktik pengalaman lapangan. Didapatkan rata-rata persentase kemampuan disposisi matematis siswa berada pada 53,01% dengan kategori cukup. Ditambah lagi terdapat siswa yang memiliki pandangan terhadap matematika sebagai suatu ilmu yang sulit dan tidak menyenangkan. Padahal, disposisi matematis sangat berpengaruh terhadap pembelajaran matematika dan prestasi siswa. Apalagi, dengan baiknya disposisi matematis siswa, maka akan mendukung mereka memandang indahnya ciptaan Tuhan melalui matematika. Hal ini menjadikan Pendekatan Matematika Realistik Indonesia (PMRI) menjadi alternatif solusi terhadap permasalahan disposisi matematis. Tujuan dari penelitian adalah untuk mengetahui apakah penerapan PMRI dapat mengembangkan kemampuan disposisi materi aljabar dan mendeskripsikan penerapan PMRI dalam mengembangkan kemampuan disposisi matematis siswa pada materi aljabar dengan menggunakan metode kualitatif deskriptif. Hasil dan simpulan penulisan ini menunjukkan bahwa kemampuan disposisi matematis siswa setelah PMRI diterapkan mengalami peningkatan dengan rata-rata hasil persentase menjadi 61,48% dengan kategori baik. Hasil persentase yang meningkat ini disebabkan oleh indikator disposisi matematis yang terdapat pada keseluruhan sintaks PMRI. Dengan demikian, indikator-indikator tersebut dapat terasah di setiap sintaks. Berkaca dari penerapan PMRI ini, disarankan agar penerapannya dapat dilakukan lebih dari dua kali dan menggunakan media pembelajaran fisik.